2019
DOI: 10.1249/mss.0000000000001784
|View full text |Cite
|
Sign up to set email alerts
|

Individual Variability in Waist Circumference and Body Weight in Response to Exercise

Abstract: Purpose This study aimed to determine the magnitude of exercise-induced individual variability for waist circumference (WC) and body weight change after accounting for biological variability and measurement error. Determinants of response variability were also considered. Methods Participants (53 ± 7.5 yr) were 181 adults (61% women) with abdominal obesity randomized to the following: control; low-amount, low-intensity exercise (LALI); high-amount, low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 29 publications
1
25
1
1
Order By: Relevance
“…Occasionally, some studies have compared the prevalence of responders or non‐responders between different exercise intervention programs with the aim of knowing the most appropriate an effective design for the prevention/treatment of obesity or other obesity‐related comorbidities. Several studies in adults provided data of the interindividual variability in variables such as body composition or other health outcomes, while there is scarce evidence in the pediatric population . Our group has shown that the addition of supervised exercise to a family‐based lifestyle education program resulted in significantly greater reduction of percentage HF (≈20%) in children with overweight/obesity .…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Occasionally, some studies have compared the prevalence of responders or non‐responders between different exercise intervention programs with the aim of knowing the most appropriate an effective design for the prevention/treatment of obesity or other obesity‐related comorbidities. Several studies in adults provided data of the interindividual variability in variables such as body composition or other health outcomes, while there is scarce evidence in the pediatric population . Our group has shown that the addition of supervised exercise to a family‐based lifestyle education program resulted in significantly greater reduction of percentage HF (≈20%) in children with overweight/obesity .…”
Section: Introductionmentioning
confidence: 83%
“…Interindividual variability exists after pharmacological, nutritional, or exercise interventions: whereas some participants improve in one or several outcomes after an intervention (responders), others do not change or even worsen their response (non‐responders) to the intervention . However, this information is rarely provided, and the vast majority of published studies only report the results as overall mean values .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note in Table 1 and Figure 1 how the group differences in the observed mean response lead to group differences in the observed numbers of responders, adverse responders and trivial responders (according to a response threshold of 5 ml kg −1 min −1 and an adverse response threshold of −5 ml kg −1 min −1 ). Therefore, although researchers have made inferences relating to response heterogeneity or 'trainability' on the basis of such 'responder counts' (Bonafiglia, Ross, & Gurd, 2019;Hammond et al, 2019;Ross, de Lannoy, & Stotz, 2015;Williams et al, 2019), it is in fact the group differences in mean treatment response that explain the differences in responder counts between our groups (Figure 1), besides the fact that the responder counts cannot be correct in the first place. Therefore, such group comparisons of responder counts do not provide much information about response heterogeneity, as defined in the context of precision medicine (Section 2).…”
Section: Comparing Responder Counts Between Samplesmentioning
confidence: 91%
“…Recently, Hammond et al (2019) speculated that the SD of change comparison approach is 'questionable' when 'the control group is contaminated with other sources of variability, beyond that of which is random' . This statement denotes a lack of appreciation of the difference between systematic and random sources of variance.…”
Section: (I) How Should a Negative Sdir Be Interpreted?mentioning
confidence: 99%